Pharmacokinetics, exposure, efficacy and safety of obinutuzumab in rituximab‐refractory follicular lymphoma patients in the GADOLIN phase III study. Issue 9 (12th July 2019) - Gibiansky, Ekaterina; Gibiansky, Leonid; Buchheit, Vincent; Frey, Nicolas; Brewster, Michael; Fingerle‐Rowson, Günter; Jamois, Candice
Abstract : Aims: Rituximab is standard care in a number of lymphoma subtypes, including follicular lymphoma (FL), although many patients are resistant to rituximab, or develop resistance with repeated treatment, and a high proportion relapse. Obinutuzumab is a novel anti‐CD20 monoclonal antibody with improved efficacy over rituximab. It is approved for previously untreated chronic lymphocytic leukaemia (CLL), and for use with bendamustine in patients with rituximab‐relapsed/refractory FL. Methods: Using a previously described population pharmacokinetic (PK) model of obinutuzumab in patients with non‐Hodgkin lymphoma and CLL, we conducted an exposure‐response analysis using data from 6 clinical trials in patients with CD20+ B‐cell malignancies (CLL11, GADOLIN, GATHER, GAUDI, GAUGUIN and GAUSS) to describe the PK properties of obinutuzumab, identify covariates influencing exposure, and explore how exposure affects safety, efficacy and pharmacodynamics. Results: A 2‐compartment model with linear and time‐dependent clearance described obinutuzumab PK. Disease type and subtype, body weight, baseline tumour size, and sex had the largest effects on PK. Obinutuzumab exposure was not associated with occurrence or severity of adverse events, but higher exposure appeared to be associated with greater efficacy, particularly longer progression‐free survival. However, in multivariate Cox regression analysis, progression‐free survival benefit in the obinutuzumab plus bendamustine arm was independent of exposure. Conclusion: The updated population PK model reported here accurately describes the PK of obinutuzumab patients with non‐Hodgkin lymphoma and CLL. The selected obinutuzumab dosing regimen offers clinical benefit in a majority of rituximab‐refractory FL patients treated with bendamustine, irrespective of variability in exposure, whilst minimising adverse events.